반응형
$(1+x)^{\frac{1}{2}}$ 는 $\left| x \right | <1 $ 일 때 다음과 같이 전개할 수 있다.
$$(1+x)^{\frac{1}{2}} = 1 + \frac{1}{2} x + (-\frac{1}{8})x^2 + ... $$
일반적으로, $(1+x)^{m}$ 은
$$(1+x)^{m} = 1+mx + \frac{m}{2!}x^2 + \frac{m(m-1)(m-2)}{3!} x^3 + ... \\ =\sum_{n=0}^{\infty} \frac{m!}{n!(m-n)!}x^n = \sum_{n=0}^{\infty} {}_m \mathrm{C}_n x^{n} $$
으로 표현할 수 있다.
예제로써,
$$ (1+x)^{-\frac{3}{2}} = {}_{-\frac{3}{2}} \mathrm{C}_0 + {}_{-\frac{3}{2}} \mathrm{C}_1 x^1 + {}_{-\frac{3}{2}} \mathrm{C}_2 x^2 +... \\ = 1 + -\frac{3}{2} x + \frac{-\frac{3}{2}(-\frac{3}{2}-1)}{2!} x^2 + ... \\ = 1- \frac{3}{2} x+ \frac{15}{8} x^2 + ... $$
이다.